The Spatial and Temporal Behaviour of Particulate Matter and Submicron Particles in the Molise Region - Notardonato, Ivan; Pierno, Luigi; Cafaro, Claudia; Ceci, Paolo; Avino, Pasquale (Geographica Pannonica, 2024)
Environmental pollution and its impact on human health has become a topic of great concern. In recent years, the scientific community has significantly increased its attention towards the protection of human health and an increasing number of analytical determinations are being carried out on food and environmental matrices to guarantee their quality. Within these determinations, the monitoring of air quality, both in indoor and outdoor environments, is of particular scientific interest. In particular, the presence of micrometric particles, atmospheric particulate matter (PM) and ultrafine particulate matter (UFP) has become a marker of air quality in recent years. The study of these substances is particularly important since the diameter of the particles is inversely proportional to their ability to penetrate the respiratory system. In places of greatest attendance and areas with high vehicular traf fic, units are installed for continuously monitoring the air quality. This paper aims to bring a snapshot of the concentrations of these particles in Molise, a small region in Italy. The results obtained present rather limited PM10, PM4, PM2.5, PM1 and UFP ranges, especially as regards Campobasso, the regional capital.